Cross-Talk Between Histone Methyltransferases and Demethylases Regulate REST Transcription During Neurogenesis - Swaminathan, Jyothishmathi; Maegawa, Shinji; Shaik, Shavali; Sharma, Ajay; Bravo-Alegria, Javiera; Guo, Lei; Xu, Lin; Harmanci, Arif; Gopalakrishnan, Vidya (Frontiers in Oncology, 2022)
The RE1 Silencing Transcription Factor (REST) is a major regulator of neurogenesis and brain development. Medulloblastoma (MB) is a pediatric brain cancer characterized by a blockade of neuronal specification. REST gene expression is aberrantly elevated in a subset of MBs that are driven by constitutive activation of sonic hedgehog (SHH) signaling in cerebellar granular progenitor cells (CGNPs), the cells of origin of this subgroup of tumors. To understand its transcriptional deregulation in MBs, we first studied control of Rest gene expression during neuronal differentiation of normal mouse CGNPs. Higher Rest expression was observed in proliferating CGNPs compared to differentiating neurons. Interestingly, two Rest isoforms were expressed in CGNPs, of which only one showed a significant reduction in expression during neurogenesis. In proliferating CGNPs, higher MLL4 and KDM7A activities opposed by the repressive polycomb repressive complex 2 (PRC2) and the G9A/G9A-like protein (GLP) complex function allowed Rest homeostasis. During differentiation, reduction in MLL4 enrichment on chromatin, in conjunction with an increase in PRC2/G9A/GLP/KDM7A activities promoted a decline in Rest expression. These findings suggest a lineage-context specific paradoxical role for KDM7A in the regulation of Rest expression in CGNPs. In human SHH-MBs (SHH-and SHH-) where elevated REST gene expression is associated with poor prognosis, up- or downregulation of KDM7A caused a significant worsening in patient survival. Our studies are the first to implicate KDM7A in REST regulation and in MB biology.